2010
DOI: 10.1159/000290040
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Lipopolysaccharide Reduces Social Behavior in Male Offspring

Abstract: Objective: This study investigated the relationship between maternal sickness behavior during pregnancy and offspring development and behavior. Methods: Pregnant Wistar rats were administered with lipopolysaccharide (LPS, 100 µg/kg, i.p.) on gestation day (GD) 9.5. Dams’ sickness behavior was analyzed, and at birth, offspring number and weight were evaluated. Male offspring was evaluated through physical development, play behavior, adult social interaction, plus maze studies and morphological analysis of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
102
4
21

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 99 publications
13
102
4
21
Order By: Relevance
“…Fifty-two rats (13 from each group; i.e., males and females from the control and LPS groups) were evaluated in the elevated plus maze 2 h after the LPS challenge on PND60-70. The test was performed as previously described (Kirsten, Taricano, Maiorka, et al, 2010). Briefly, the apparatus consisted of two opposing open arms (50 cm long, 10 cm wide) and two opposing closed arms (50 cm long, 10 cm wide, (Hogg, 1996).…”
Section: Elevated Plus Mazementioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-two rats (13 from each group; i.e., males and females from the control and LPS groups) were evaluated in the elevated plus maze 2 h after the LPS challenge on PND60-70. The test was performed as previously described (Kirsten, Taricano, Maiorka, et al, 2010). Briefly, the apparatus consisted of two opposing open arms (50 cm long, 10 cm wide) and two opposing closed arms (50 cm long, 10 cm wide, (Hogg, 1996).…”
Section: Elevated Plus Mazementioning
confidence: 99%
“…For example, prenatal treatment with LPS (100 µg/kg, intraperitoneally [i.p. ], on gestational day [GD] 9.5) in rats impairs social behavior (play behavior) in both infancy and adulthood in male but not female offspring (Kirsten et al, 2012;Kirsten, Taricano, Maiorka, Palermo-Neto, & Bernardi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the offspring of mothers forced to exercise during gestation demonstrated an increased entry to the open arms in elevated plus maze test indication a reduced anxiety behavior [9]. LPS treatment has been previously shown to decrease the social behaviors, however, no effects has been reported on elevated plus maze test [10]. In the present study, offspring of LPS treated and exercised mothers demonstrated increased amount of time spent at the closed arms in elevated plus maze test compared to the offspring of PLS treated sedentary mothers.…”
Section: Discussionmentioning
confidence: 91%
“…O estudo das proles destas mães mostrou que os mesmos apresentavam alterações comportamentais compatíveis com aquelas descritas para o autismo, sugerindo que este poderia ser um modelo animal de autismo ( KIRSTEN et al, 2010;KIRSTEN et al, 2011;KIRSTEN et al, 2012;). O tratamento com zinco uma hora após a administração da endotoxina preveniu estas alterações (KIRSTEN et al, 2015a).…”
Section: Discusãounclassified
“…Para a injeção do LPS, foi escolhido o dia 9,5 da gestação a partir dos estudos de Kirsten et al (KIRSTEN et al, 2010;KIRSTEN et al, 2011) mostrando que a endotoxina prenatal administrada neste dia promove comportamento autista-simile na prole de ratas.…”
Section: Discusãounclassified